Environmental Literacy: Perception of Prospective Biology Teacher Students on Waste Management in FKIP Untan - Susanti, Mirna Dewi; Afandi, Afandi; Tenriawaru, Andi Besse (Universitas Tanjungpura, 2024)
This research aims to analyze the perceptions of prospective biology teacher students regarding waste management in the FKIP Tanjungpura University environment. Descriptive methods with a quantitative approach are used to describe the current state of research subjects based on existing facts. The research population consisted of prospective biology teacher students from the 2016, 2017 and 2018 classes, with a sample size of 124 students selected randomly. The research instrument consists of a questionnaire and environmental literacy test questions. The research results show that prospective biology teacher students at FKIP Tanjungpura University have a good perception of waste management, with the majority of students showing positive environmental attitudes and high commitment to environmentally friendly practices. Environmental literacy in this research is explained through three main indicators: environmental knowledge, attitudes and behavior. From the research results, it can be concluded that students show a good understanding of the concept of waste management and awareness of the importance of protecting the ecosystem. In conclusion, this research provides a clear picture of the perceptions of prospective biology teacher students regarding waste management in the campus environment. This collective support from students reflects the importance of environmental literacy in preserving the environment. Efforts to continue to increase environmental understanding and awareness among students can make a positive contribution in creating a generation that cares about the environment in the future.